The relationship of commitment, communication, trust and extent of collaboration in tourism network - Ibrahim, Amlus; Che Mat, Ruzinoor; Ramayah, T.; Boey, Julie Chyaw In; Saad, Abd. Rahim (Universiti Utara Malaysia Press, 2007)
In an island economy like Penang, tourism plays a major role in the economy of the island.One area that has not been fully explored is the collaboration of these tourism industry players in the network of tourism service providers.This paper explores the impact of commitment, communication and trust on the extent of collaboration within the tourism network.Responses was elicited using a structured questionnaire from tourism operators mainly from hotels, travel agencies, transportation companies for land, sea and air mode, vehicle rental shops, tourist attraction spots operators, souvenirs or local nature product shops and others such as restaurants, destination management center, vacation clubs and government tourism organization. A total of 90 responses were received.The findings show that, extent of communication was the only important predictor of extent of collaboration whereas commitment and trust was not.These points to the importance of communication in the multi player network of tourism. Implications are forwarded as a conclusion.